ANALISIS SEAKEEPING DAN OPERABILITAS KAPAL PATROLI UNTUK PERBAIKAN SISTEM LAMPU ANCANG BANDARA TEPI LAUT - Ikang Martin Trasnowo; Mardi Santoso; Sumardiono . (Proceedings Conference on Marine Engineering and its Application, 2023)
The maintenance of the swaying light system requires fast handling to meet the proceduralneeds of aviation. Therefore it is necessary to carry out an in-depth analysis of seakeeping andoperability to reduce the risk of ship delays when needed when sudden swaying lights are repaired.Movements caused by external forces acting or sea waves will affect the comfort and safety of the crewand passengers of the ship itself. Ship movement response is a seakeeping parameter that must beconsidered to support the feasibility of ship design.In this final project, the seakeeping analysis processuses Maxsurf Motion software to generate ship movement values. The variations in the direction ofarrival of the waves used are 00, 450, 900, 1350, and 1800 at a speed of 20 knots. Meanwhile, variationsin significant wave height are 0,05; 0,3; 1; 2; dan 3,3 meter and wave period used are 5,6; 6,8; 7,5;10; and 11 second and ship shipping routes according to Natuna waters wave data from BMKG.Calculations are performed using Maxsurf Motions Advance software.The results that can beconcluded in this final project are the percentage of ship operability based on seakeeping criteriaaccording to Olson 1978 and the U.S Coast Guard where 94,06% is operable and 5,94% downtime. Inaddition, it can also be concluded that the operational wave height that is permitted and safe for shipssailing in the waters of the Natuna Sea is 3 meters.